The Determinants of Systematic Risk: A Firm Lifecycle Perspective (2016)
This paper investigates how of systematic risk varies over the lifecycle of the firm. If market equity beta is determined by firm characteristics as the literature on the determinants of systematic risk holds, and if those characteristics change over the lifecycle of the firm following a definite pattern as firm lifecycle theory suggests, then market equity beta should change over the lifecycle of the firm following a predictable pattern. Our findings indicate that, holding other determinants of beta constant, the coefficient of systematic risk tends to fall in magnitude following a nonlinear pattern as firm age increases. In addition, we find that the volatility of market equity beta also tends to fall over the lifecycle of the firm. We argue that our main variable of concern, i.e. firm age, proxies for variables that have hitherto been omitted in the literature on the determinants of systematic risk. In particular, we maintain that firm age may proxy for the positive reputation that firms acquire over time with shareholders. This research is useful for both practitioners and researchers in that it may suggest ways to adjust empirical estimates of systematic risk. In addition, our results are important for research on beta forecasting as they show that the length of the stationary interval of betas is shorter for young companies, so that beta forecasting may be less accurate for firms in the early stages of their lifecycle compared to beta forecasting for mature firms.